The mystic mind : the psychology of medieval mystics and ascetics - Kroll, Jerome, 1935-; Bachrach, Bernard S., 1939- (New York (N.Y.) : Routledge, 2005)
'he Mystic Mind 'is the result of a fascinating collaboration between a medieval historian and a professor of psychiatry, applying modern biological and psychological research findings to the lives of medieval mystics and ascetics. This illuminating study examines the relationship between medieval mystical experiences, and the religious practices of mortification of the body. Laceration of the flesh, sleep deprivation and extreme starvation, while undoubtedly related to cultural and religious motivations, directly produced dramatic effects upon the body and brain functioning of the heroic ascetics, that in turn brought about altered states of consciousness. Applying modern understandings of physiology, the authors demonstrate how heroic asceticism could be used to obtain a desired mystical state, as well as examining and disputing much contemporary writing about the political and gender motivations in the medieval quest for closeness with God. Drawing upon a database of 1,462 medieval holy persons as well as in-depth studies of individual saints, 'The Mystic Mind 'is essential reading for all those with an interest in medieval religion or the effects of self-injurious behaviour on the mind.
Includes bibliographical references (p. ).
Keywords: Asceticism -- Psychology; Ascetics -- Psychology; Church history -- Middle Ages, 600-1500.; Mysticism -- Psychology; Mystics -- Psychology; Psychology, Religious